A Pilot Study of Oxytocin in Low-Income Women With a Low Birth-Weight Infant: Is Oxytocin Related to Posttraumatic Stress?. (August 2019) - Garfield, Lindsey; Holditch-Davis, Diane; Carter, C. Sue; McFarlin, Barbara L.; Seng, Julia S.; Giurgescu, Carmen; White-Traut, Rosemary
Abstract : Background: Negative outcomes related to prematurity may lead to maternal distress. Mothers of premature/low birth-weight infants report increased posttraumatic stress (50%) and depressive symptoms (63%) compared with mothers of full-term infants. Low-income, minority mothers with greater posttraumatic stress and depression have an increased risk for premature/low birth-weight delivery compared with their white counterparts. Variations in the neuropeptide oxytocin are implicated in lactation, perinatal depression, and maternal behavior. Purpose: To examine the associations among posttraumatic stress, depressive symptoms, and oxytocin in a pilot sample of minority mothers with premature/low birth-weight infants in the neonatal intensive care unit (NICU). Methods: This study employed a descriptive, correlational pilot design of 8 minority, low-income mothers with premature/low birth-weight infants. Participants answered questionnaires pertaining to posttraumatic stress, depression, lactation, and demographics and oxytocin was measured. This is a substudy that added oxytocin values. Results: Four participants had elevated depressive symptoms and 5 supplied their own milk. Women who provided their own milk had lower depressive ( t = 3.03, P = .023) and posttraumatic stress ( t = 3.39, P = .015) symptoms compared with women not supplying their own milk. Women with elevated posttraumatic stress had higher levels of depressive symptoms ( r (8) = 0.8, P = .006) and lower levels of oxytocin ( r (8) = 0.77, P = .026). Implications for Practice: These results are congruent with previous literature on providing human milk and maternal mental health. In addition, we found a possible relationship between postpartum posttraumatic stress and oxytocin in minority women with premature/low birth-weight infants. NICU nurses should encourage lactation and assess mothers for posttraumatic stress and depressive symptoms. Implications for Research: Research is needed to identify the biologic milieu associated with posttraumatic stress and depression in at-risk mothers.